(untitled) (Prithvi Academic Journal, 2026)
Place attachment theory relates to the emotional and cognitive bonds people develop with a specific physical setting and is a key concept in environmental psychology. It is a popular concept in sustainable tourism development and destination branding behavior. This study aimed to explore the factors affecting destination brand-building behaviour of the residents of Pokhara through a quantitative study. A sample of 200 residents from Pokhara, Nepal, was used to conduct partial least squares (PLS) based structural equation modeling (SEM) for the test of proposed hypotheses. The study results revealed that place memory and affective attachment have a significant positive influence on destination brand-building behavior (DBBB). Furthermore, the longer the duration of residency was found to have a significant positive influence on DBBB compared to shorter residency. However, place identity, place dependence, and social bonding found no significant influence on DBBB. Furthermore, the result revealed that the dimensions of place attachment along with a dummy variable of duration collective explain 52.7 percent of the variation in DBBB. The findings indicate that destination brand-building behavior is primarily driven by emotional bonds and lived experience. The findings suggest that the destination management and local government should utilize residents with longer duration residency in branding campaigns by offering them a platform to share their emotional experiences.